Synthesis, biological evaluation, and molecular docking of combretastatin and colchicine derivatives and their hCE1-activated prodrugs as antiviral agents - Richter, Michael; Boldescu, Veaceslav; Graf, Dominik Korbinian; Bartenschlager, Ralf; Klein, Christian D. (ChemMedChem, 2019)
Recent studies indicate that tubulin can be a host factor for vector-borne flaviviruses like dengue (DENV) and Zika (ZIKV), and inhibitors of tubulin polymerization such as colchicine have been demonstrated to decrease virus replication. However, toxicity limits the application of these compounds. Herein we report prodrugs based on combretastatin and colchicine derivatives that contain an ester cleavage site for human carboxylesterase, a highly abundant enzyme in monocytes and hepatocytes targeted by DENV. Relative to their parent compounds, the cytotoxicity of these prodrugs was reduced by several orders of magnitude. All synthesized prodrugs containing a leucine ester were hydrolyzed by the esterase in vitro. In contrast to previous reports, the phenylglycine esters were not cleaved by human carboxylesterase. The antiviral activity of combretastatin, colchicine, and selected prodrugs against DENV and ZIKV in cell culture was observed at low micromolar and sub-micromolar concentrations. In addition, docking studies were performed to understand the binding mode of the studied compounds to tubulin.